Decentralisation of education in Singapore. - Kok, Pui Kum. (2008)
This paper attempts to provide some insight into the effects of decentralisation of the Singapore education system on school performance. Particularly, it highlights the difference between the independent and autonomous schools. Our empirical results although indicative, is not conclusive. Nevertheless, it recognises the success of Singapore in decentralising the education system.